AN ANALYSIS THE CHARACTERISTIC OF THE MAIN CHARACTER IN CROWN OF MIDNIGHT NOVEL BY SARAH J MASS'S - Tria Novita Br Karo Sekali; Mas Andika Fahreza; Diajeng Amelia Putri; Dharmadiah Dharmadiah; Dewi Nurmala (PHILOLOGY Journal of English Language and Literature, 2023)
The purpose of this study is to find out which characters are owned by Celaena Sardothein as the main character in the novel Crown of Midnight by Sarah J Mass, which was published by Bloomsbury on August 15, 2013. The method used in this research is a qualitative method with a descriptive type. The results of this study indicate that there are 6 characters possessed by Celaena Sardothein in the novel Crown of Midnight, namely the characters Daredevil, Clever, Cruel, Vengeful, Obey and Smart and there is a value contained in the novel Crown of Midnight, namely the value of education in the form of a sense of "responsibility".